Cos(tan^-1(x))
Cos (tan-1 x)
- print Print
- list Cite
Expert Answers
hala718
| Certified Educator
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
`cos(tan^-1 x) = 1/sqrt(1+x^2)`
If you need to prove the identity, then here are the steps.
First we will assume that arctanx = A
==> tanA = x
But we know that tanA = `sinA/cosA ` = opposite side/adjacent side= `x/1` Then we can assume that we have aright angle triangle such that the sides are x and 1.
Then, the hypotenuse is `h= sqrt(1^2+x^2)= sqrt(1+x^2).`
Now we need to find `cos(tan^-1x)`
`cos(tan^-1 x) = cos(A) =(adjacent)/h = 1/sqrt(1+x^2)` ==> `cos(tan^-1 x) = 1/sqrt(1+x^2)`
Related Questions
- Prove tan x + cos x/(1+sin x) = 1/cos x
- 1 Educator Answer
- Show that `tan^2 x = (1 - cos(2x))/(1 + cos(2x))`
- 1 Educator Answer
- Prove that `sec^4(x)-tan^4(x)=1+tan^2(x)` .
- 2 Educator Answers
- Prove that `(1 + tan x)/(1+cot x) = tan x`
- 2 Educator Answers
- Prove the identity: (cos x / (1 - sin x)) - sec x = tan x
- 2 Educator Answers